Proteomic and In Silico Analyses Highlight Complement System's Role in Bladder Cancer Immune Regulation - Korak, Tugcan; Baloglu, Ibrahim Halil; Kasap, Murat; Arisan, Elif Damla; Akpinar, Gurler; Arisan, Serdar (Mdpi, 2025)
Background and Objectives: Bladder cancer (BLCA), intimately associated with the immune system, represents a substantial global health burden due to its high recurrence rates and limited therapeutic effectiveness. Although immunotherapy shows promise, challenges persist due to the lack of reliable therapeutic targets. This study aims to investigate potential immune-related biomarkers that could influence the tumor microenvironment in BLCA, using proteomic and in silico approaches. Materials and Methods: Tissue samples from BLCA patients (n = 27) and controls (n = 27) were collected from & Scedil;i & scedil;li Hamidiye Etfal Training and Research Hospital. Proteomic analysis was performed by liquid chromatography/mass spectrometry (LC-MS)/MS to reveal the identities of differentially regulated proteins. Protein network analysis and hub protein detection were performed using Cytoscape (v.3.10.3), while functional annotation was carried out using EnrichR. The immunological analysis of hub proteins was performed in Sangerbox platform, and prognostic associations were evaluated through the Kaplan-Meier Plotter tool. Results: LC-MS/MS analysis identified 120 differentially regulated immune-related proteins. STRING analysis, using an immune response dataset (GO:0006955), highlighted the complement cascade as a significantly enriched pathway (p < 0.05). Proteins, namely C4A, CFB, C4B, C8B, CFH, CFI, C5, C4BPA, C3, and C2, that are known to play key roles in the complement system were identified. Immunological analysis with these proteins revealed the phenomena of immune infiltration and immune checkpoint gene associations (p < 0.05). Four hub genes-CFB, C4B, CFI, and C2-demonstrated a significant prognostic value for BLCA (p < 0.05). Conclusions: This study highlights the pivotal role of the complement system in the immune regulation of BLCA. CFI, C4A, and C4B emerged as potential target proteins for BLCA treatment, particularly in immunotherapy, for enhancing survival. Future research on these proteins and the complement system specifically focusing on BLCA may facilitate the development of targeted immunotherapies, ultimately improving treatment outcomes.
Keywords: bladder cancer; complement system; prognosis; proteomics; tumor immune microenvironment